A multifunctional silver nanocomposite for the apoptosis of cancer cells and intracellular imaging. Issue 41 (8th May 2017) - Zhang, Ting-Ting; Yang, Fan; Li, Xiang-ling; Zhao, Wei; Xu, Jing-Juan; Chen, Hong-Yuan
Abstract : A multifunctional silver nanoparticle based nanocomposite for specific cancer cell therapy and in situ imaging. Abstract : A multifunctional Ag NP based nanocomposite was fabricated which realized accurate targeting of specific cancer cells and completely initiative therapy without any photoexcitation.